No Shame for the Sun : Lives of Professional Pakistani Women - Haeri, Shahla (Karachi Oxford University Press, 2004)
Six candid interviews introduce readers to a class of Muslim women rarely acknowledged in the West. The book aims to shed light on the status, conflicts and social realities of educated Muslim women in Pakistan. They tell of the conflicts and compromises with family and community.
Include Index and Appendix
Keywords: Women in the Professions -- Pakistan